Empirical Modeling and Its Applications - Habib, Mamun (IntechOpen, 2016)
Empirical modeling has been a useful approach for the analysis of different problems across numerous areas/fields of knowledge. As it is known, this type of modeling is particularly helpful when parametric models, due to various reasons, cannot be constructed. Based on different methodologies and approaches, empirical modeling allows the analyst to obtain an initial understanding of the relationships that exist among the different variables that belong to a particular system or process. In some cases, the results from empirical models can be used in order to make decisions about those variables, with the intent of resolving a given problem in the real-life applications. This book entitled Empirical Modeling and Its Applications consists of six (6) chapters.